Danazol a new perspective in the treatment of htlv-l associated myelopathy (preliminary report) - Ailton Melo; Luciana Moura; Ana Meireles; Gerçonita Costa (Arquivos de Neuro-Psiquiatria)
We investigated the efficacy of danazol treatment in eight patients with HTLV-l associated myelopathy/tropical spastic paraparesis (HAM/TSP). Treatment with danazol yielded clinical improvement of urinary control and gait disturbances in 7 out of the 8 patients. The improvement was noted within 15 days of danazol administration. Analysis of factors of relevance to the clinical improvement with danazol showed that the beneficial response was preferentially found in females.